Ghost cell odontogenic carcinoma with suspected cholesterol granuloma of the maxillary sinus in a patient treated with combined modality therapy: A case report and the review of literature. Issue 7 (February 2018) - Qin, You; Lu, Yanwei; Zheng, Liduan; Liu, Hong
Abstract: Rationale: Ghost cell odontogenic carcinoma (GCOC) is a rare malignant odontogenic tumor with aggressive growth characteristics. Patient concerns: A 41-year-old Chinese male visited our hospital in 2013, with a 4-month history of bloody purulent rhinorrhea with a peculiar smell in the right nasal cavity. Diagnoses: The patient suffered from recurrent GCOC with suspected cholesterol granuloma of the maxillary sinus. The patient was incorrectly diagnosed with a calcifying epithelial odontogenic tumor at his first recurrence. Physical examination, radiological examination, and histopathology were used to identify GCOC. Interventions: Considering the recurrence of GCOC and poor effects of single surgery, postoperative adjuvant chemotherapy and concurrent chemoradiotherapy were performed after radical surgical excision. Outcomes: So far, no significant evidence has suggested recurrence or metastasis after a long-term follow-up. Lessons: We advocate wide surgery with clean margins at the first accurate diagnosis. Combined modality therapy could be taken for the recurrent GCOC. We expect to provide a new treatment strategy to prevent the growth of this neoplasm.